Video game market segmentation based on user behavior - Khaleghi, K.; Lugmayr, Artur (2012)
Games excited generations in various societies: from the very simple physical form - to the latest generation of digital games - in the world where we are living. They always played an important role in every aspect of human life. The initial forces behind games where means as social interaction, pure entertainment, edutainment, or simply to have fun. However, from the initial forces, games emerged towards a tool for empowering creativity and the game industry turned into a largely profitable industry. Within the scope of this paper, we describe the key findings that are indicating the common trends in gaming industry, we evaluate key technologies contributing to the game industry, and try to understand game preferences of game players and the specifics of behavioral patterns in different game genres. © 2012 ACM.